2020
DOI: 10.1021/jacs.9b11707
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Enzyme Dynamics upon Multipoint Covalent Immobilization Leads to Stability-Activity Trade-off

Abstract: The successful incorporation of enzymes into materials through multipoint covalent immobilization (MPCI) has served as the foundation for numerous advances in diverse fields, including biocatalysis, biosensing, and chemical weapons defense. Despite this success, a mechanistic understanding of the impact of this approach on enzyme stability has remained elusive, which is critical for realizing the full potential of MPCI. Here, we showed that the stabilization of lipase upon MPCI to polymer brush surfaces result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 62 publications
7
67
1
Order By: Relevance
“… 12 In a subsequent publication, by the same group, it was found that there is a trade-off in this system – more protein–polymer attachments resulted in higher stability but lower activity due to decreased motion in the folded state of the protein. 13 This experimental result conflicts with recent work on soluble chymotrypsin conjugates, where MD models showed more motion in the conjugate with the lowest enzymatic activity, a manifestation of a measured decrease in the substrate binding constant, K m . 14 …”
Section: Introductioncontrasting
confidence: 88%
“… 12 In a subsequent publication, by the same group, it was found that there is a trade-off in this system – more protein–polymer attachments resulted in higher stability but lower activity due to decreased motion in the folded state of the protein. 13 This experimental result conflicts with recent work on soluble chymotrypsin conjugates, where MD models showed more motion in the conjugate with the lowest enzymatic activity, a manifestation of a measured decrease in the substrate binding constant, K m . 14 …”
Section: Introductioncontrasting
confidence: 88%
“…In particular, our results highlight the fact that the structural integrity of surface immobilized enzymes is no guarantee that the enzyme will remain functional, and that the systems' internal dynamics should be specifically investigated before drawing any conclusions regarding the conservation of the catalytic activity. The mechanical perturbations obtained for RNase A grafted on various surfaces (and with various orientations) illustrate the stability-activity tradeoff that was recently observed13 by Weltz et al(53) using single-molecule FRET imaging. Altogether our modeling approach provides a simple tool to help understand how protein adsorption might impact their dynamics and function, especially when one needs to achieve a delicate balance between an enzyme stability and its catalytic activity.…”
supporting
confidence: 73%
“…The enzyme stability relies both on the reversibility and valency of the enzyme-carrier interaction. It is widely accepted [6,7] and lastly supported by singlemolecule experiments [53], that irreversible multivalent attachments contribute to the structural stabilization of immobilized enzymes. Semproli et al demonstrated that one transaminase from Vibrio fluvialis immobilized through glyoxyl chemistry on agarose porous microbeads works 22 fold more efficiently in flow (5.35 mg product x mg enzyme -1 x h -1 ) than in batch [54].…”
Section: Introductionmentioning
confidence: 97%